The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1207/s15327027hc1602_2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Empathy in Responses to Persuasive Risk Communication: Overcoming Resistance to HIV Prevention Messages

Abstract: This article offers a theoretical analysis of the role of empathy as a key mediator of the suasive effects of health messages, and it discusses the testing of an empirical tool for studying the state of empathy in responses to persuasive messages. It is argued that felt empathy evokes cognitive and emotional processing conducive to important health-promoting responses. This assertion was tested by operationalizing empathy as a response state via a new measure, the Empathy Response Scale (ERS). Two pilot tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(114 citation statements)
references
References 30 publications
4
106
0
3
Order By: Relevance
“…Identification with characters in narratives may also increase perceived susceptibility to cancer and empathy for those with cancer. Campbell and Babrow found that empathy mediates the relationship between exposure to HIV prevention messages and perceptions of HIV risk (95), and Shelton and Rogers showed, in a nonhealth-related study, that empathy-arousing appeals can facilitate attitude change (96). Finally, perceived similarity to narrative characters may influence one's perception of social norms regarding cancer-related behaviors.…”
Section: Other Moderating Factors That May Enhance or Diminish Narratmentioning
confidence: 99%
“…Identification with characters in narratives may also increase perceived susceptibility to cancer and empathy for those with cancer. Campbell and Babrow found that empathy mediates the relationship between exposure to HIV prevention messages and perceptions of HIV risk (95), and Shelton and Rogers showed, in a nonhealth-related study, that empathy-arousing appeals can facilitate attitude change (96). Finally, perceived similarity to narrative characters may influence one's perception of social norms regarding cancer-related behaviors.…”
Section: Other Moderating Factors That May Enhance or Diminish Narratmentioning
confidence: 99%
“…The word empathy is derived from empatheia in Greek -meaning "feeling into" (Campbell & Babrow, 2004) and is described as the ability to experience vicariously the feelings of others (M. Hoffman, 1977), or sharing the subjective experience of others (Campbell & Babrow). Empathy is not considered an emotion and is not on Plutchik's wheel of emotions (Plutchik, 2001), which includes joy, trust, fear, surprise, sadness, disgust, anger and anticipation, as well as their opposites.…”
Section: Emotion and Empathymentioning
confidence: 99%
“…This high degree of cognitive engagement (i.e., "high involvement" processing) would theoretically sustain counterpersuasion efforts (e.g., friends and family's negative reactions) and would result in temporal persistence and predicted behavioral outcomes (e.g., influenza immunization). 28,29 Yet, strong affective evaluations of information may also occur with emotional responses invoked especially due to the incongruence such action poses to strongly held vaccine beliefs (i.e., cognitive dissonance) among racial and ethnic minorities. 26 Given the challenges associated with improving maternal immunization coverage among this vulnerable population, this study sought to test 2 forms of targeted persuasive messaging models in comparison to generic influenza Vaccine Information Statements (VIS) developed by the CDC.…”
Section: -21mentioning
confidence: 99%